2014
DOI: 10.1080/09593330.2013.879495
|View full text |Cite
|
Sign up to set email alerts
|

Optimization for the removal of orthophosphate from aqueous solution by chemical precipitation using ferrous chloride

Abstract: The precipitation reaction between the orthophosphate and Fe2+ ions was studied to describe the optimum condition for the removal of orthophosphate from the aqueous solution. The effects of pH, Fe:P molar ratio, and alkalinity were evaluated for the initial orthophosphate concentrations in the range from 1.55 to 31.00 mg/L - PO4(3-) -P. The optimum pH was found to be 8.0 in all orthophosphate concentration ranges. When the stoichiometric moles of Fe2+ were added, the removal efficiencies were significantly les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The average molar Fe/P ratio in the influent tank was only 1.27 and 0.85 at the period when FeCl 2 concentration was 15 and 30 mg l -1 , respectively (Table 3). An et al (2014) investigated the formation of vivianite in synthetic wastewater with FeCl 2 dosing and found that the Fe/P molar ratio should be more than 3 to enable significant vivianite formation. The authors attributed this to the partial formation of ferrous hydroxides, which hindered the formation of vivianite.…”
Section: Verification Of the Effect Of Fecl 2 Dosing On Solids Concenmentioning
confidence: 99%
See 1 more Smart Citation
“…The average molar Fe/P ratio in the influent tank was only 1.27 and 0.85 at the period when FeCl 2 concentration was 15 and 30 mg l -1 , respectively (Table 3). An et al (2014) investigated the formation of vivianite in synthetic wastewater with FeCl 2 dosing and found that the Fe/P molar ratio should be more than 3 to enable significant vivianite formation. The authors attributed this to the partial formation of ferrous hydroxides, which hindered the formation of vivianite.…”
Section: Verification Of the Effect Of Fecl 2 Dosing On Solids Concenmentioning
confidence: 99%
“…The role of iron in the flocculation (Higgins and Novak, 1997) and floc destruction under anaerobic conditions (Novak et al, 2003) has been reported, but its impact on OSA performance has not been systematically studied. Iron salts are commonly added to wastewater in full-scale plants for phosphorous removal by chemical process (Paul et al, 2001;An et al, 2014). When Fe(II) salt is added to an aerobic reactor, iron is spontaneously oxidised to Fe(III) given the availability of oxygen in the system (i.e., 2Fe 2+ + 2H + + ½O 2 2Fe 3+ + 2H 2 O, E°c ell = +2.0 V).…”
Section: Introductionmentioning
confidence: 99%
“… 20,21 In spite of everything, methylene blue is surely one of the most used dye in textile industries and, for this reason, the developing of new strategies for the efficient removal from water effluents is still ongoing and of great interest. 22–27 The common methods for the removal of organic dyes include: chemical oxidation or reduction, 28 precipitation, 29 ion exchange, 30 electrolysis, 31 photo-catalytic processes, 32,33 membrane filtration, 34 ozonation, 35 degradation, 36 bio-sorption 37 and adsorption. 38,39 In particular, adsorption is one of the most used techniques because it relies on a simple mechanism, does not produce handling problems, and the process can be reversible.…”
Section: Introductionmentioning
confidence: 99%
“…However, during the ZVI corrosion process Fe 2+ is released and strongly influences the physicochemical properties of the system [11]. Fe 2+ can reduce the biogenic sulfide due to pyrite precipitation (FeS 2 ), but can also interact with other anions, notably bicarbonate and phosphate, to form siderite (FeCO 3 ) and vivianite (Fe 3 (PO 4 ) 2 •8H 2 O) [12]. Vivianite precipitation entraps the soluble P released upon AD.…”
Section: Introductionmentioning
confidence: 99%